2018
DOI: 10.1002/ange.201806039
|View full text |Cite
|
Sign up to set email alerts
|

Der Mackay‐Cluster [Cu43Al12](Cp*)12: Ein offenschaliges 67‐Elektronen‐Superatom mit metallähnlicher elektronischer Struktur

Abstract: Der paramagnetischeC luster [Cu 43 Al 12 ](Cp*) 12 entsteht bei der Reaktion von [CuMes] 5 mit [AlCp*] 4 (Cp* = h 5 -C 5 Me 5 ;M es = Mesityl). Dieser ausschließlich durchK ohlenwasserstoff-Liganden stabilisierte "magische" Cluster mit 55 Atomen im Clusterkern weist eine ummantelte Ikosaeder-Struktur des Mackay-Typs auf.D ie Superatomkonfiguration von 67 Elektronen und offener Valenzschale ist einzigartig, wobei drei ungepaarte Elektronen schwacha ntibindende Jellium-Zustände besetzen. Diese Situation deutet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…Also, there is no linear variation of magnetic susceptibility (between 5 K and 300 K) or significant magnetic moment change in magnetic field up to 20 000 Oe on superconducting quantum interference device (SQUID; Supporting Information, Figures S13, S14). These results indicate Cu 53 has a closed‐shell electronic configuration with a non‐magic electron count …”
Section: Resultsmentioning
confidence: 91%
“…Also, there is no linear variation of magnetic susceptibility (between 5 K and 300 K) or significant magnetic moment change in magnetic field up to 20 000 Oe on superconducting quantum interference device (SQUID; Supporting Information, Figures S13, S14). These results indicate Cu 53 has a closed‐shell electronic configuration with a non‐magic electron count …”
Section: Resultsmentioning
confidence: 91%
“…[105] An even larger,n ovel NiGa cluster [Ni 8 Ga 6 ](Cp*) 6 with a > b and a + b @ n is obtained in the reaction of [Ni(cdt)] (cdt = 1,5,9-Cyclododecatrien) with GaCp* proceeding via the isolable,a nd fully characterized intermediate [Ni(cdt)-(GaCp*)]. [107] Despite the unusually high degree of disorder of the central nickel core which precluded ar eliable determination of its core geometry,t he overall Ni 8 Ga 6 core structure was found to be (distantly) related to structural motifs frequently observed in binary NiGa phases.Q uite similarly,t he structure of the first truly intermetalloid example of acluster [M a E b ](Cp*) n with a + b @ n,[Cu 43 Al 12 ]-(Cp*) 12 (Figure 15), [107] features aM ackay-type two-shell icosahedral core,astructural motif which is commonly found in quasicrystalline phases of related compositions, like ternary copper aluminide systems. [108] Quantum chemical calculations revealed the exceptional open-shell superatomic electron configuration of the system with an unusually high electron count of 67 electrons,w hereat the high reactivity associated with such an electronic configuration was anticipated to be contained within the spherical capsule of the twelve,s terically shielding Cp* ligands.…”
Section: Hume-rothery Phase-inspired Molecular Coordination Chemistrymentioning
confidence: 84%
“…[95] Angewandte Chemie Reviews of the compound with benzonitrile further revealed striking resemblance of its surface reactivity to catalytically relevant semi-hydrogenation reactions at Hume-Rothery nanophases, like Fe 4 Al 13 ,o rb inary PdGa-and NiGa-phases. [107] Despite the unusually high degree of disorder of the central nickel core which precluded ar eliable determination of its core geometry,t he overall Ni 8 Ga 6 core structure was found to be (distantly) related to structural motifs frequently observed in binary NiGa phases.Q uite similarly,t he structure of the first truly intermetalloid example of acluster [M a E b ](Cp*) n with a + b @ n,[Cu 43 Al 12 ]-(Cp*) 12 (Figure 15), [107] features aM ackay-type two-shell icosahedral core,astructural motif which is commonly found in quasicrystalline phases of related compositions, like ternary copper aluminide systems. [105] An even larger,n ovel NiGa cluster [Ni 8 Ga 6 ](Cp*) 6 with a > b and a + b @ n is obtained in the reaction of [Ni(cdt)] (cdt = 1,5,9-Cyclododecatrien) with GaCp* proceeding via the isolable,a nd fully characterized intermediate [Ni(cdt)-(GaCp*)].…”
Section: Low-valent and Other Molecular Precursorsmentioning
confidence: 99%
See 2 more Smart Citations